La corresponsabilidad parental y su indebida aplicación sobre el principio de interés superior del menor - Zanzzi Barona, Kevin Alejandro (2021)
The present research project aims to analyze the inapplicability of the right of parental responsibility of judges specialized in family matters in hearings, violating the principle of the best interests of the minor, since through the decisions issued the preference can be verified that is given to the mother at the time of granting custody and custody of the minor, leaving the father of the family with the right to adhere to a visiting schedule and to comply with a monthly alimony, violating the principle of equality. It will be possible to appreciate with statistical data, theories and surveys such as the code of childhood and adolescence affects the principle of superior interest and compile the necessary information on how the family specialist judges omit the application of these rights at the time of issuing their decisions to favor of the mother and finally propose a reform so that the right of co-responsibility is mandatory in equal rights and responsibilities for the father and mother in order to safeguard the best interests of the minor..........